Impact of One Year Covid-19 on Hand and Upper Extremity Injury: A Cross-Sectional Study - Tito Sumarwoto; Pamudji Utomo; Naufal Aminur Rahman; Mochammadsyah Beizar Yudhistira (Journal Orthopaedi and Traumatology Surabaya, 2022)
Background: On March 11, 2020, the World Health Organization declared the COVID-19 outbreak a worldwide pandemic. On March 31, 2020, Indonesia enacted a large-scale societal limitation. As a result, the number of patients seeking medical treatment for emergencies has decreased significantly. Home and fall accidents were the leading causes of a hand injuries, and this trend is anticipated to persist throughout the epidemic. Despite this, there is scarce information about the many forms and causes of hand and upper extremity injuries. This research aimed to see how COVID-19 affected hand and upper extremity injuries.Methods: The observational cross-sectional research was undertaken from March 2019 to February 2021. The Pre-COVID-19 phase was measured from March 2019 to February 2020, while the COVID-19 period was measured from March 2020 to February 2021. Patients who presented to Prof. Dr. R. Soeharso Orthopedic Hospital with hand and upper and lower extremity injury-related diagnoses from the emergency unit, outpatient, or inpatient were included in the study.Results: The overall number of patients in this study was 2644, with a mean total number of patients of 141.83 (SD 43.21) in the pre-COVID-19 era and 78.5 (SD 32.55) in the COVID-19 era, a significant reduction (p 0.001).Conclusion: There is a substantial drop in hand and upper extremity injury patients during the timespan of COVID-19 compared to the Pre-COVID-19. The findings might aid in the development of new ways for better understanding the service provisions needed in the case of injury during a pandemic.